2021
DOI: 10.1021/jacsau.1c00109
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Origin of Nanopore Current Blockage for Volume Difference Sensing at the Atomic Level

Abstract: Changes in the nanopore ionic current during entry of a target molecule underlie the sensing capability and dominate the intensity and extent of applications of the nanopore approach. The volume exclusion model has been proposed and corrected to describe the nanopore current blockage. However, increasing evidence shows nonconformity with this model, suggesting that the ionic current within a nanopore should be entirely reconsidered. Here, we revisit the origin of nanopore current blockage from a theoretical pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 45 publications
1
57
1
Order By: Relevance
“…Previous works verified that non‐covalent interactions between the nanopore sensing interfaces and targets could be manipulated to support accurate distinction of peptides/proteins [23,31,32]. Recently, a study demonstrated theoretically and experimentally the possibility of non‐covalent interactions between a nanopore and analytes in regulating the current blockages [33]. Several available strategies were proposed to decelerate translocation speeds of peptides/proteins to acquire the nanopore current recording at high signal‐to‐noise ratios [24,34–37].…”
Section: Introductionmentioning
confidence: 99%
“…Previous works verified that non‐covalent interactions between the nanopore sensing interfaces and targets could be manipulated to support accurate distinction of peptides/proteins [23,31,32]. Recently, a study demonstrated theoretically and experimentally the possibility of non‐covalent interactions between a nanopore and analytes in regulating the current blockages [33]. Several available strategies were proposed to decelerate translocation speeds of peptides/proteins to acquire the nanopore current recording at high signal‐to‐noise ratios [24,34–37].…”
Section: Introductionmentioning
confidence: 99%
“…According to our previous studies, the R1 constricted region (T218 ∼ D222 and T274 ∼ S278) at the entrance of AeL determines the selectivity of the nanopore. 27–31 The introduction of charged residues at R1 achieved a charge selective AeL sensor. 32…”
Section: Resultsmentioning
confidence: 99%
“…Another major difference among the channels is the value of the parameter Eb${E_b}$. As discussed previously, the simplest interpretation of this empirical parameter is the membrane binding energy of αSyn; however, the value of Eb${E_b}$ can also be affected by anomalously slow unbinding kinetics introduced by disordered membrane binding domains [24], as well as by electrostatic or chemical association between the polyanionic C‐terminal domain and the net positively charged VDAC pore lumen [1, 63, 64]. Of these, only the latter is clearly channel‐specific and suggests a difference in the pore/polypeptide association energy between VDAC/αSyn and MspA/αSyn of about 70.28emkBT$7\;{k_B}T$.…”
Section: Discussionmentioning
confidence: 99%